Built local interpolation cubic spline function - Kurbonov Jaloliddin (Science and Education, 2024)
To analyze the spline function with a higher order of approximation based on the given data, to solve the problem in the object on the basis of experimental data by the working group in order to eliminate the problem that occurred in an object. Based on the experimental data obtained to solve the given problem, a mathematical model focused on this object is built, and based on the built model, the solution to the problem in the object is determined and analyzed.